Calçando estratégias lúdicas: jogos, brinquedos e brincadeiras indutores para o ensino-aprendizado do sapateado na faixa etária de 7 a 10 anos - MOTA, Thais Malato (2019)
This course conclusion work aimed to propose inducing playful strategies for teaching-learning the north american tap dance through games, toys and frolic. The locus of this research was Igreja Projeto Vida, located in the neighborhood of Terra Firme, Belém / PA. Eight children aged 7 to 10 years participated. Bring to this research based theory psychomotor, from the theorists, Alves (2008) and Gallahue and Ozmum (2005), whose studies dealing with the childs‟s development and approach on the psychomotor aspects, considering the motor coordination, the rhythmic perception, the balance, the laterality, for the motor, psycho-social and affective development of the child. In the area of playfulness was used the author Andrade (2013), whose studies turn to the importance of game and play. From the tap dance studies I bring the literary work ‟Sapateado: Vivências na Universidade‟‟, by the authors Teixeira (2016) and Oliveira (2016), whose studies approach teaching possibilities and outline methodological strategies. The methodology developed is directed towards action research in a qualitative descriptive approach. As a final result was presented nine playful strategies as inductors for the teaching of tap dance, through the playfulness.